Effect of Laundry Soap Containing Linear Alkyl Benzene Sulfonate on Protein and Cellular Metabolic Activity of Gills and Liver Primary Cell Culture of Shield head Fish (Synodontis schall) - Muzn Tarig Khalid Abdurahim; Shima Elfadel Ahmed Hassan (African Journal of Advanced Pure and Applied Sciences, 2024)
One of the main sources of chemical water pollutants for fish is the laundry soap that we use in our daily lives without adequate treatment to remove harmful compounds. The present study aimed to develop cost-effective bioassays to study the effects of laundry soap containing linear alkyl benzene sulfonate on Shield Head Fish (Synodontis Schall) gills and liver primary cell culture. The primary cell culture was carried out following a method modified by Gaurav et al. [1] It was cultured in petri dishes containing omega-3 medium. The bioassays were carried out when the culture reached up to 100% confluence in 24 days by using four different concentrations of laundry soap (10 mg/ml, 5 mg/ml, 2.5 mg/ml, and 1.25 mg/ml) for 48 hours to observe changes in protein biomass and cellular metabolic activity. The results showed no significant difference in protein concentration between doses. These changes were in direct correlation with the dose value, but cell viability decreased with increased doses on gills and liver primary cells as determined by reducing the MTT reagent to formazan indicating a potential concern for the health of fish and aquatic invertebrates. The study suggests using Omega-3 as a growth medium for primary cell cultures and candle smoke to promote cell growth and as a source of carbon dioxide. There must be more research on purifying water and separating harmful substances from it and efforts must be made to create environmentally friendly soap from natural materials.